PERAN WANITA USAHATANI TANAMAN HIAS TERHADAP PENDAPATAN KELUARGA MISKIN DI DESA TOLOMBUKAN KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - Cristi S. Lumbu; Juliana R. Mandei; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study was to determine the role of ornamental plant farming women in poor families in Tolombukan Village, Pasan District, Southeast Minahasa Regency. The research was conducted for three months, from December to February 2020. The data used are primary data obtained through interviews with 20 women who are farming ornamental plants. Secondary data were obtained from the Tolombukan Village Office. The data analysis used is descriptive, contribution formula and the data is presented in tabular form. The role of women as main breadwinners if it has greater than 50 percent. The results showed that the role of women as wives who cultivated ornamental plants in Tolombukan Village was as additional breadwinners and not the main breadwinners for their families.Â